2016
DOI: 10.1017/s147895151600064x
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual beliefs, practices, and needs at the end of life: Results from a New Zealand national hospice study

Abstract: As a result of our study, which was the first nationwide study in NZ to examine spirituality in hospice care, Hospice New Zealand has developed a spirituality professional development program. Given that spirituality was found to be important to the majority of our participants, it is hoped that the adoption of such an approach will impact on spiritual care for patients and families in NZ hospices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 34 publications
(45 reference statements)
0
32
0
2
Order By: Relevance
“…The majority of studies were conducted in North America (n=26),19–44 with 11 from Europe,45–55 7 from Oceania4 56–61 and 6 from Asia 62–67. Participants were sampled from hospice settings (inpatient and hospice at home) in 27 studies,4 19 25 26 28–35 38–40 45–47 53 54 56–58 60–62 66 acute and long-term care settings in 9,22 27 44 55 59 63–65 67 general practices settings in 3,42 48 52 cancer centres in 4,23 24 36 37 a mix of settings in 3 studies21 49 50 and palliative care centres in 2 studies 43 51. One study provided no details on where participants were recruited from 41.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies were conducted in North America (n=26),19–44 with 11 from Europe,45–55 7 from Oceania4 56–61 and 6 from Asia 62–67. Participants were sampled from hospice settings (inpatient and hospice at home) in 27 studies,4 19 25 26 28–35 38–40 45–47 53 54 56–58 60–62 66 acute and long-term care settings in 9,22 27 44 55 59 63–65 67 general practices settings in 3,42 48 52 cancer centres in 4,23 24 36 37 a mix of settings in 3 studies21 49 50 and palliative care centres in 2 studies 43 51. One study provided no details on where participants were recruited from 41.…”
Section: Resultsmentioning
confidence: 99%
“…For 10 datasets, studies were included where they reported that the majority of patients (ie, ≥50%) had died within a year or before study completion 23 24 26 27 31 34 36 39 46 59 61. Twenty-one datasets included participants with a mix of chronic conditions,19 21 25 28–33 39–45 47–50 53 54 56–58 61 18 datasets included only participants with cancer,4 20 23 24 26 27 34–37 46 51 52 59 60 62–67 and 1 dataset included participants with only neurodegenerative diseases 55. Two datasets did not specify participants’ conditions 22 38…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations